Introduction to fingerprint verification - Hameed, Shihab A.; Badurik, Waleed A. (IIUM Press, 2011)
Fingerprint biometric is one of the essential, widely used and accepted biometrics. It has been used as a form of identification for a long time and considers an acceptance and fear. Fingerprints consider by people as unique and can be used to identify someone. This trust comes from governmental and law enforcement use of fingerprints. At the same time, their use of the fingerprint also causes fear about its use. Some individuals involved with fingerprint authentication for network access have expressed the feeling that using their fingerprint for authentication makes their feel like criminals. This feeling can lead to fear of the use of fingerprint biometrics. The use of biometrics must be accompanied with proper user training and communication. By doing so, biometrics can be seen as a privacy-enabling technology, not a technology to be feared. Even with the concern over the use of fingerprints, the finger biometric still remains more widely accepted than any other biometric